2019
DOI: 10.1101/748467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Body height in young adult men and risk of dementia later in adult life

Abstract: This study examined the relationship between body height and dementia and explored the impact of intelligence level, educational attainment, early life environment and familial factors. A total of 666,333 men, 70,608 brothers, and 7,388 twin brothers born 1939-1959 and examined at the conscript board were followed in Danish nationwide registers . Cox regression models were applied to analyze the association between body height and dementia. Within-brothers and withintwin pair analyses were conducted to explor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Mounting evidence from cohort studies also suggests that stature might be an independent predictor of cognitive function 4,8,14,36–38 . Furthermore, a case–control study has shown that people in the highest quartile have a reduced risk of Alzheimer's disease by 59% compared with the lowest quartile 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence from cohort studies also suggests that stature might be an independent predictor of cognitive function 4,8,14,36–38 . Furthermore, a case–control study has shown that people in the highest quartile have a reduced risk of Alzheimer's disease by 59% compared with the lowest quartile 39 .…”
Section: Discussionmentioning
confidence: 99%
“…This is in conflict with some previous epidemiological studies. Increased adult height has reported associations with better cognitive performance and reduced risk of AD [39][40][41], which may relate to increased cognitive reserve associated with the larger head circumference or better nutrition leading to greater height and reduced AD risk [39]. Moreover, individuals with impaired lung function have been reported to have a higher risk of cognitive decline and dementia [42,43].…”
Section: Trait Associations With Polygenic Riskmentioning
confidence: 99%